2014
DOI: 10.1002/jmv.23968
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of distinct populations of hepatitis C virus in the liver and plasma of patients co‐infected with HIV and HCV

Abstract: Viral diversity is an important predictor of hepatitis C virus (HCV) treatment response and may influence viral pathogenesis. HIV influences HCV variability in the plasma; however, limited data on viral variability are available from distinct tissue/cell compartments in patients co-infected with HIV and HCV. Thus, this exploratory study evaluated diversity of the hypervariable region 1 (HVR1) of HCV in the plasma and liver for 14 patients co-infected with HIV and HCV. Median intra-patient genetic distances and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 113 publications
2
3
0
Order By: Relevance
“…This complex pattern of within-host envelope gene evolution during chronic HCV infection supports the findings of previous studies (32, 51, 52) that used sequencing technologies with a lower depth. Here, we show that even with a greater sequencing depth, not all HCV lineages are detected at all times, which is consistent with the hypothesis of compartmentalization in the liver or in extrahepatic tissues giving rise to distinct HCV subpopulations (53)(54)(55)(56)(57).…”
Section: Discussionsupporting
confidence: 89%
“…This complex pattern of within-host envelope gene evolution during chronic HCV infection supports the findings of previous studies (32, 51, 52) that used sequencing technologies with a lower depth. Here, we show that even with a greater sequencing depth, not all HCV lineages are detected at all times, which is consistent with the hypothesis of compartmentalization in the liver or in extrahepatic tissues giving rise to distinct HCV subpopulations (53)(54)(55)(56)(57).…”
Section: Discussionsupporting
confidence: 89%
“…In particular, a clear serum compartmentalization was observed for the patients having pre‐transplant samples. This result is in accordance with other studies which showed different viral populations between serum and liver . This finding could be attributed, among other causes, to: (i) the existence of slow replication or defective variants in the liver that would be less represented among circulating variants, (ii) a difference in HCV variant clearance rates, and/or (iii) the contribution of the extrahepatic viral replication.…”
Section: Discussionsupporting
confidence: 92%
“…The characteristics of the four patients analyzed are expressed in Table 1. A total of 414 cloned sequences were obtained and an average of 17 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) sequences from each sample for both of the genomic regions analyzed (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the woodchuck model, it was demonstrated that at low replication rates, the virus is predisposed to invade the PBMC compartment leading to occult viral infection and even primary hepatocellular carcinoma in 20% of infected animals [17,18,43]. Viral infection of immune cells is a well-recognized immune escape strategy, and due to lower levels of viral replication as well as unique cellular and biological conditions, the virus may evolve differently, as was found in studies of other hepatotropic and lymphotropic viruses such as hepatitis C virus [44] and the human immunodeficiency virus [45][46][47][48]. These studies highlight the potential clinical impact of HBV variability in plasma vs PBMC warranting further investigation.…”
Section: Discussionmentioning
confidence: 99%